The Effect of Ratio of Yoghurt with Red Fleshed Guava Extract and Stabilizer Ratio on The Quality of Soft Candy - Andy Wijaya; Herla Rusmarilin; Zulkifli Lubis (Universitas Sumatera Utara, 2013)
This research was conducted to find the effect of ratio of yogurt with red fleshed guava extract and stabilizer ratio on the quality of soft candy. The research had been performed using factorial completely randomized design with two factors, i.e ratio of yogurt with red fleshed guava extract (Y): (40%:60%), (30%:70%), (20%:80%), and (10%:90%), and stabilizer ratio (seaweed:carrageenan) (A) : (1:4), (2:3), (3:2), and (4:1). Parameters analyzed were moisture content, vitamin C content, total acid, total soluble solid (TSS), protein content, total microbe, and organoleptic values (colour, flavor and taste, and texture). The results showed that the ratio of yogurt with red fleshed guava extract had highly significant effect on moisture content, vitamin C content, total acid, total soluble solid (TSS), protein content, total microbe, and colour, flavor and taste, and texture. Stabilizer ratio also had highly significant effect on moisture content, vitamin C content, total acid, total soluble solid (TSS), protein content, total microbe, colour, flavor and taste, and texture. The interaction of the two factors had highly significant effect on vitamin C content, protein content, and texture. The ratio of yogurt with red fleshed guava extract of 20%:80% and stabilizer ratio of (1:4) produced the best quality of soft candy